Risk Assessment Of Adverse Drug Reactions In Elderly Patients With Chronic Diseases: English - Godeliva Adriani Hendra; Eva Monica; Ike Yossy Herawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: The adverse drug reaction (ADR) is 4-7 times more common in elderly patients. That was also related to changes in pharmacokinetics and pharmacodynamics that triggered the emergence of Drug-Related Problems. Objective: The purpose of this study was to assess ADR in elderly patients with chronic diseases using the GerontoNET Score and the Screening Tool of Older People's Prescriptions (STOPP) criteria. Methods: The research design used a cross-sectional study which was analyzed descriptively. The sample consisted of 72 patients, aged more than 60 years, accompanied by chronic diseases, and hospitalized at Waluyo Jati Kraksaan Hospital. The exclusion criteria were patients referred to the Intensive Care Unit. Assessment to see the risk of ADR in elderly patients with chronic diseases using the GerontoNet Score while the wrong type of drug is given to elderly patients using the STOPP criteria. The variables contained in the GerontoNET Score are comorbid conditions ³4 (score= 1), heart failure (score= 1), liver disease (score = 1), the number of drugs such as: £5 (score= 0); 6-7 (score=1); ³8 (score=4), history of ADR (score=2), kidney failure (score=1). Results: The variable with the most ADR risk factors was the number of drugs ³8 drugs as many as 47 patients (65.3%) with GerontoNET score ³4 as much as 70.8%. The types of drugs included in the STOPP criteria are clopidogrel, Arixtra (fondaparinux), beta-blockers, NSAIDs, and furosemide. Conclusion: The risk factor for ADR was the number of drugs ³8 drugs.